Cardiac Tuberculosis on 18F-FDG PET Imaging—A Great Masquerader of Cardiac Sarcoidosis - Sumati Sundaraiya (Thieme Medical and Scientific Publishers Pvt. Ltd., 2021)
A young gentleman with suspected cardiac sarcoidosis and LV dysfunction whose CMR revealed multifocal subepicardial to mid myocardial linear enhancement in the left ventricular myocardium underwent cardiac 18F-FDG PET imaging. The images revealed patchy regions of increased FDG uptake involving the apical to mid anterolateral, mid to basal anteroseptal/ right ventricular and mildly increased FDG uptake in apical inferior segments of the LV myocardium concordant with CMR findings. Whole body PET CT imaging showed multiple hypermetabolic supra and infra diaphragmatic lymphadenopathy, with no pulmonary lesion identified. Biopsy from the left para aortic lymph node revealed necrotizing granulomatous inflammation consistent with tuberculosis. Based on the histopathological findings of the lymph nodes, diagnosis of cardiac tuberculosis was made, given the similar imaging appearances in both sarcoidosis and TB. This case highlights that cardiac TB although rare, should be included in the differential diagnosis in patients with suspected infiltrative cardiomyopathy, particularly in TB endemic regions.